Newspaper advertising as a source for the history of Kazan industry in the second half of the XIX century - GALANIN, S. F; HAKIMOVA, A. S; GALANINA, S. S; VALEEV, R. M (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT The research is based on a combination of quantitative methods allowing to consider newspaper advertising as a specific kind of mass historical source and qualitative approach to observation of individual advertising materials. There were formal features pointed out of the quantitative approach allowing joint separate advertising materials in groups to discover regularity. Newspaper advertising was one of such methods of the reaction and reflected the peculiarities of the enterprise’s behavior on the market. The vast majority of newspaper advertising manufacturers are the announcement of craft enterprises. Newspaper advertising is in many ways a unique source that characterizes Russian business practices. RESUMEN La investigación se basa en una combinación de métodos cuantitativos que permiten considerar la publicidad en periódicos como un tipo específico de fuente histórica masiva y un enfoque cualitativo para la observación de materiales publicitarios individuales. Hubo características formales señaladas en el enfoque cuantitativo que permitieron que los materiales publicitarios conjuntos por separado en grupos descubrieran regularidad. La publicidad en los periódicos fue uno de esos métodos de reacción y reflejó las peculiaridades del comportamiento de la empresa en el mercado. La gran mayoría de los fabricantes de publicidad en periódicos son el anuncio de empresas artesanales. La publicidad en los periódicos es, en muchos sentidos, una fuente única que caracteriza las prácticas comerciales rusas.